NAṢR HĀMID ABŪ ZAYD AND SAHIRON SYAMDUDDIN'S HERMENEUTICAL INTERPRETATION ON VERSE OF JIHĀD (Al-ANKABŪT/29: 69) - Afifah, Tsaqifa Aulya (Peminat Ilmu Ushuluddin, 2024)
The verses of the Qur'an interpreted by the commentators, both classical and modern, continue to experience changes and developments. This is done to achieve the goal of the Qur'an which is ṣho>liḥ li kulli zama>n wa makan. It is not surprising that the methods of interpreting the Qur'an are very diverse in order to increase the intensity of academic research to obtain variations in the meaning of the Qur'an in an integrative manner. This study focuses on the meaning of Jihad as stated in QS. Al-Ankabut: 69. This study discusses the interpretation of two figures, Hermenutika Sahiron Syamsuddin and Nasr Hamid Abu Zayd. The questions that will be examined by this paper are how do the two figures think in interpreting the verses of jihad and how is the analysis of the interpretation of the verses of jihad by the two figures? To answer these questions, the author uses a qualitative research type, while the nature of this research is descriptive-analytical. The method used to process and analyze the data in this study is a combination of deductive-inductive-comparative. The results of this study reveal that both figures deny the existence of a textual interpretation of the jihad verse which is only interpreted in the context of war. According to Syamsuddin, the meaning of jihad in Surah al-Ankabu>t/29: 69 can be seen in three stages: first, jihad against one's own lusts to achieve the path of obedience to Allah. Second, jihad against those closest to us. Third, jihad against the government, state, and homeland. Meanwhile, Zayd through his hermeneutics (tafsir al-siya>qi) explains that the meaning of jihad in Surah al-Ankabu>t/29: 69 is to free the country from all its problems.